Parametric study on thermal and hydraulic characteristics of inter-connected parallel and counter flow mini-channel heat sink. (5th May 2019) - Tikadar, Amitav; Oudah, Saad K.; Paul, Titan C.; Salman, Azzam S.; Morshed, A.K.M.M.; Khan, Jamil A.
Highlights: Numerically studied overall performance of inter-connected mini-channel heat sink. Inter-connected counter flow mini-channel shows improved thermal performance. Maximum 31.83% reduction of friction factor is achieved at Re   =  1 50. Maximum 36.43% enhancement of Nu is recorded at Re   =   1044. Maximum PEC value of 1.33 is achieved at Re   =   1044. Abstract: The paper presents three-dimensional numerical investigation of fluid flow and heat transfer performance of parallel and counter flow mini-channel heat sink where cross flow between parallel channels was enabled with inter-connectors. The aspect ratio (height to width) and hydraulic diameter of the investigated mini-channel were 0.33 and 750 µm respectively. In this study, water was employed as the coolant, and the flow was in the single-phase regime under laminar flow condition at Reynolds numbers ranging from 150 to 1044. A constant heat flux of 20 W/cm 2 was applied at the bottom surface of the heat sink. To analyze the effect of cross flow on the overall thermo-hydraulic performance of the mini-channel heat sink, five different widths of the inter-connector were studied. The non-dimensional pressure, velocity, temperature, friction factor, overall Nusselt number (Nu), and thermal resistance were calculated to evaluate the overall performance of the inter-connected mini-channel heat sink. Finally, the performance of the inter-connected mini channel was compared with the conventional mini-channel by calculating the performance evaluation criteria (PEC). The results show that the inter-connector has a significantly larger effect on the counter flow mini-channel heat sink compared with the parallel flow mini-channel. For the counter flow mini-channel heat sink, Nu was enhanced by a maximum of 36% at Re = 1044 as compared to the conventional parallel flow mini-channel while a maximum of 31.13% reduction in friction factor was recorded at Re = 150. The PEC of the counter flow mini-channel went up to 1.33, and its value shows an increasing trend with as Reynolds number increases.